GAYA KOMUNIKASI DAN KETERAMPILAN BERBAHASA GURU BAHASA INGGRIS DALAM MENCIPTAKAN IKLIM ORGANISASI DI SMK PENERBANGAN HASANUDDIN MAKASSAR - Anwar, Khairil (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This research is a form of research that uses quatitative, data collection techniques carried out in this study are questionnaires to students for their perceptions in seering the commination style and skills of English teacher in the learning process, this includes limits only on students within the scope of the school and direct interview process, the sample of this study was taken 60 level X-ADM and X-AP people from 115 level X people (ADM, AP, and EA). From the results of research and discussion conducted obtained communication style (X1) and language skills (X2) have a significant effect jointly on the climate of the school organization in Hasanuddin. Flight vocation school Makassar because communication style and language skills can produce a climate of school organization that are skills and able to produce students are skilled and prosicient in English in accordance with the ideals of the school in producing alumni who are ready to use in the world of work.